Does Corruption Really Affect the Growth of Entrepreneurship in Zimbabwe? - Muzurura, Joe (International Journal of Emerging Trends in Social Sciences, 2019)
Like in most developing countries, the level of entrepreneurship growth as measured by the number of new firm start-ups has become a central economic issue in Zimbabwe. Necessity and opportunity-driven entrepreneurial activities in the country are being driven by weakening economic growth, poverty, idiosyncratic macro-uncertainties and high levels of unemployment. The country has consistently been listed by the Transparent International Perception of Corruption Index as one of the most corrupt countries in Sub-Saharan Africa outside a war zone. The study examined the nexus between entrepreneurial activities and corruption in Zimbabwe using Ordinary Least Regression equation for the period 1998 to 2016. Our findings suggest that productive entrepreneurial activities in Zimbabwe are significantly being curtailed by regressive tax regimes coupled with enfeebled public institutions. We also demonstrate a positive one way causality running from entrepreneurial activities to corruption and, hence proving the applicability of the greasing hypothesis of corruption in Zimbabwe. The study recommends a number of policy prescriptions that include: reducing levels of taxes on entrepreneurial activities, eliminating red-tape and regulations that add costs on opportunity-driven entrepreneurship, increasing the effectiveness of public institutions especially those that deal with entrepreneurs, introducing robust legislation aimed at reducing public officials’ opportunities for rent seeking in entrepreneurial activities that are most prone to corrupt practices. In addition, there is need to monitor bureaucrats and impose severe penalties in order to make corruption payoffs too risky. Our study contributes to the literature on the greasing effect of corruption on entrepreneurial activities in developing countries.